(untitled) (REMUNOM, 2025)
The incidence of depressive disorders in the population is high. Postpartum depression (PPD) is defined as a mood disorder that usually begins in the first four weeks after delivery and can be mild and transient, neurotic, and even psychotic. Major depression occurs for a minimum period of two weeks, with the presence of depressive mood or anhedonia associated with at least four of the symptoms. to describe the importance of the pharmacist in the treatment of postpartum depression. The methodology was based on an integrative literature review. Data collection was performed in the following databases: Virtual Health Library (BVS) and the National Library of Medicine (PubMed) from September to May 2025. The descriptors used are indexed in the Health Sciences Descriptors (DeCS) platform and their equivalents in English, through the Medical Subject Heading (MeSH). To join the terms, “AND” will be chosen as the Boolean operator. To compose this review, information is presented regarding the 9 articles contained in the discussion of this literature review. Depression is a psychiatric condition with high worldwide prevalence, affecting more than 340 million people, according to recent estimates. The postnatal phase involves intense hormonal, social and psychological changes, predisposing women to depressive episodes. In addition to changes in sleep, appetite and libido, symptoms such as persistent sadness, anguish, feeling unable to care for the baby, suicidal ideation and, sometimes, thoughts of harming the child stand out. This study identified through the literature that postpartum depression is a debilitating condition that requires a multimodal approach for screening and treatment.